On distortion of waves in a nonlinear magnetoelastic conductor - Chakraborty, S. (Archives of Mechanics, 1998)
Wave distortion and formation of shocks due to the elastic nonlinearity of the medium in the presence of a magnetic field are studied using the multiple scales technique for a one-dimensional travelling longitudinal wave. Condition for formation of shocks has been obtained for a sinusoidal signal.